+0  
 
0
392
2
avatar

9-5(-3z+8k) use k= -2 and z= 6

Guest Jul 11, 2014

Best Answer 

 #2
avatar+93346 
+5

Re: 9-5(-3z+8k) use k= -2 and z= 6

$$9-5(-3*6+8*-2)\\\\
=9-5(-18-16)\\\\
=9-5(-34)\\\\
=9+5*34\\\\
=9+170\\\\
=179$$

Melody  Jul 12, 2014
 #1
avatar
0

9-5(-3z(6) + 8k(-2))

4+(-9+(-16))

4+(-25)

-21

Guest Jul 11, 2014
 #2
avatar+93346 
+5
Best Answer

Re: 9-5(-3z+8k) use k= -2 and z= 6

$$9-5(-3*6+8*-2)\\\\
=9-5(-18-16)\\\\
=9-5(-34)\\\\
=9+5*34\\\\
=9+170\\\\
=179$$

Melody  Jul 12, 2014

24 Online Users

avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.